MiR-200c promotes papillary thyroid cancer cell proliferation, migration, and invasion by downregulating PTEN. (December 2021) - Guo, Kun; Wang, Jialiang; Shu, Ling; Zhou, Guangjun
Highlights: MiR-200c was upregulated in papillary thyroid cancer and predicted poor clinical prognosis in patients. Overexpression of miR-200c could promote the proliferation, migration and invasion of papillary thyroid cancer cells. MiR-200c exerts its oncogenic role in papillary thyroid cancer via targeting PTEN. Abstract: MiR-200c has been reported in several types of human cancer. Nevertheless, the expression profile and biological functions of miR-200c remain uncovered papillary thyroid cancer (PTC). The expression level of miR-200c was evaluated in PTC tissues using RT-qPCR. Survival analysis was performed in a cohort of 88 PTC patients. The effects of miR-200c on cell proliferation, migration, and invasion capacities were analyzed using CCK-8 and transwell assays. Target genes of miR-200c were assessed using luciferase reporter assay, RT-qPCR, Western blot and rescue experiments. MiR-200c was found to be upregulated in human PTC tissues and closely associated with pN stage and distant metastasis. High expression of miR-200c was associated with poor clinical prognosis in PTC patients. Whilst overexpression of miR-200c was demonstrated to promote the proliferation, migration, and invasion of PTC cells; knockdown of miR-200c showed an opposite inhibitory effect. Bioinformatics analysis and luciferase reporter assays confirmed that PTEN is a downstream target of miR-200c. Functional assays demonstrated that PTC cell proliferation, migration, and invasion were promoted by miR-200c via negative regulation of PTEN. Finally, overexpression of PTEN was shown to partially reverse the tumor promoting effect of miR-200c. In conclusion, this study indicates that miR-200c is a crucial prognostic biomarker of PTC, and that targeting of miR-200c/ PTEN axis may be of therapeutic significance in PTC patients.